Demographic correlates, lifestyle habits, and health effects of poor sleep quality in Indian adolescent girls living in a second-tier city - Suganya Rajendran,; Parihar, Akhilendra Singh; Monica Lazarus, (Asian Journal of Medical Sciences, 2024)
Background: Insufficient sleep, poor sleep quality, and sleepiness are common problems related to learning, memory, and school performance. During puberty, sleep habits change earlier among girls in parallel to their earlier pubertal maturity. The changes occur during adolescence in response to maturational changes and increased autonomy and independence. Aims and Objectives: This study aims to estimate the prevalence of poor sleep quality among adolescent girls in a second-tier city. Materials and Methods: Cross-sectional observational study conducted in 150 school-going adolescent girls from three different schools in a second-tier city. The study was conducted using the Pittsburgh Sleep Quality Index scale for assessment of the quality of sleep and an investigator designed pro forma to analyze various lifestyle habits. Kutcher Adolescent Depression Scale 6 was used to address the depressive symptoms. Results: Prevalence of poor sleep quality was 9.2%. Pre-bed screen time of >30 min was found in 53% of girls with poor sleep quality. Overweight girls also have poor sleep quality. Good grades (>90% marks in examinations) were associated with poor sleep quality. About 8.3% of girls with poor sleep quality have one or more symptoms pertaining to depression. Conclusion: The pre-bed screen time of more than 30 min in the form of any electronic screens leads to poor sleep quality and poor sleep quality is significantly associated with being overweight. Poor sleep quality is also associated with some symptoms of depression. These all are observed in the girls living in a tier two city, awareness among adolescent girls must be spread to decrease the screen time and they should also be encouraged for better sleep hygiene.